Gestão de pessoas: a motivação como ferramenta de melhoria em tempos de crise - CARVALHO, Dênis Fernandes Silva; SILVA, Jussara Roberta da; SHIMITE, Nathan Martins; SILVA, Talita dos Santos (115, 2020)
Neste projeto, mostraremos a motivação como ferramenta de melhoria em tempos de crise, como ter resultados positivos a curto e longo prazo utilizando de todas as ferramentas motivacionais em sincronia, as maneiras de lidar dentro do ambiente de trabalho, quais são os problemas mais recorrentes, os riscos e o preço de um funcionário desmotivado, além de mostrar como o gestor e os empregados podem compreender e utilizar da motivação para alavancar seus resultados. Assim como os benefícios da rotatividade, o gerenciamento de pessoas e como as novas ferramentas de motivação são tão importantes para o sucesso da empresa, valorizando seus objetivos e reconhecendo talentos e ideias inovadoras, transformando os problemas em soluções, investindo assim, no maior capital que uma empresa possui: O capital Humano. Ao final, você estará preparado para solucionar diversos problemas humanos com um melhor gerenciamento, com um suporte vasto e levando sua empresa ao caminho do sucesso, obtendo o melhor de cada um. “É preciso conhecer para atender, motivar para crescer” - Denis Carvalho

The growth of a company, regardless of its size, depends a lot on the performance of its employees and, therefore, on the effectiveness of people management and its resources. Consequently, getting to know and understand your team well is essential to develop the motivation of each one, through it, the chance of your venture remaining in the market and managing to grow is much greater. In addition, it considerably reduces the chances of absenteeism, drop in production, accidents and incidents related to demotivation in the workplace. "It is necessary to know so you can attend, motivate so you can grow" - Dênis Carvalho. In this TCC, we will show motivation as an improvement tool, the benefits of turnover, people management, and how the new motivation tools are so important to leverage the company's success, value its goals and recognize innovative talents and ideas, transforming employees problems in solutions, investing in the biggest capital that a company has: Human capital. You will know what people management is, its characteristics, how to develop motivation in your company, bring together sectors, styles and competencies within the teams, what employees find most important, how to detect problems and find the best strategy to solve them. Most importantly, you will learn to develop motivation at work! In the end, you will be prepared to solve several human problems with better management, with a broad support and leading your company to the path of success in a much more motivating and efficient way
People management: motivation as a tool for improvement in times of crisis
Keywords: Administração de recursos humanos; Motivação; Gestão e Negócios